The Legal Consequences for Victims in Illegal Online Loan Agreements - Kasmanto Rinaldi (JURNAL AKTA, 2023)
Technological developments touch the financial sector to produce a new innovative product called illegal online loans. Behind the convenience and practicality of illegal online loans, there are negative impacts that arise. The large growth of illegal online loans in Indonesia makes this a serious problem. The reason is because illegal online loans cause losses to victims and commit crimes in their operations. Illegal online loans have no legality in operation. So this creates new legal consequences in this matter. The purpose of this research is to look at the legal consequences of illegal online loan agreements. The method used in this research is a qualitative research method. The results of this study are that illegal online loans do not fulfill the legal terms of the agreement in accordance with the provisions contained in article 1320 of the Civil Code. So the agreement is considered invalid and never existed. However, victims of illegal online loans still have the obligation to pay their debts to illegal online lenders as a form of responsibility.